2022
DOI: 10.3389/fonc.2022.862806
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Induced Paradoxical PI3K Pathway Activation in PTEN-Competent Colorectal Cancer: Implications for Therapeutic PI3K/mTOR Inhibition

Abstract: PurposeTumor-microenvironment interactions are important determinants of drug resistance in colorectal cancer (CRC). We, therefore, set out to understand how interactions between genetically characterized CRC cells and stromal fibroblasts might influence response to molecularly targeted inhibitors.TechniquesSensitivity to PI3K/AKT/mTOR pathway inhibitors of CRC cell lines, with known genetic background, was investigated under different culture conditions [serum-free medium, fibroblasts’ conditioned medium (CM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
2
1
0
Order By: Relevance
“…36,37 In addition, PTEN was confirmed to inhibit the cell growth via inactivation of Akt signaling. 38,39 Consistently, this research found exosomes derived from hypoxic glioma cells could 40 and our study was similar to this previous research. Smad7 was known to be an inhibitor of cancer cell invasion, and its overexpression could inhibit the malignant behavior of cancer cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…36,37 In addition, PTEN was confirmed to inhibit the cell growth via inactivation of Akt signaling. 38,39 Consistently, this research found exosomes derived from hypoxic glioma cells could 40 and our study was similar to this previous research. Smad7 was known to be an inhibitor of cancer cell invasion, and its overexpression could inhibit the malignant behavior of cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“… 36 , 37 In addition, PTEN was confirmed to inhibit the cell growth via inactivation of Akt signaling. 38 , 39 Consistently, this research found exosomes derived from hypoxic glioma cells could reduce the expression of PTEN and upregulate the level of p-Akt in TMZ-treated glioma cells. Meanwhile, Zhu et al found miR-106a-5p could promote the tumorigenesis of gastric cancer through targeting Smad7, 40 and our study was similar to this previous research.…”
Section: Discussionsupporting
confidence: 69%
“…Human melanoma A375 and M14, non-small cell lung cancer (NSCLC) H460, and breast adenocarcinoma MDA-MB-231 cell lines were maintained in RPMI-1640 complete medium (Euroclone, Milan, IT) containing 10% inactivated fetal bovine serum (FBS) (GIBCO, ThermoFisher Scientific, Waltham, MA, USA), 1% L-glutamine (Euroclone) and 100 µg/ml penicillin/streptomycin (Euroclone). Human foreskin fibroblasts (HFF), purchased by ATCC and green fluorescent protein (GFP)-labeled HFF, kindly provided by Dr Fabiana Conciatori [ 26 ] were maintained in DMEM complete medium (Euroclone) supplemented with 10% FBS, 1% L-glutamine and 100 µg/ml penicillin/streptomycin. Cell lines were routinely tested for mycoplasma contamination and authenticated.…”
Section: Methodsmentioning
confidence: 99%